Freshwater mussels (Bivalvia: Unionidae) from the rising sun (Far East Asia): phylogeny, systematics, and distribution - Lopes-Lima, Manuel; Hattori, Akimasa; Kondo, Takaki; Hee Lee, Jin; Ki Kim, Sang; Shirai, Akihisa; Hayashi, Hironori; Usui, Taira; Sakuma, Kanta; Toriya, Taishi; Sunamura, Youhei; Ishikawa, Haruki; et al. (Molecular phylogenetics and evolution, 2020)
[Display omitted] •Unionidae freshwater mussels were surveyed comprehensively in Far East Asia.•Voucher specimens and tissue snips were collected for genetics.•COI barcoding and species delineation methods are applied to all genera.•New phylogeny and systematics of the Far East Unionidae are provided.•Biogeographic and conservation considerations are provided. Freshwater mussels (Bivalvia: Unionidae) is a diverse family with around 700 species being widespread in the Northern Hemisphere and Africa. These animals fulfill key ecological functions and provide important services to humans. Unfortunately, populations have declined dramatically over the last century, rendering Unionidae one of the world’s most imperiled taxonomic groups. In Far East Asia (comprising Japan, Korea, and Eastern Russia), conservation actions have been hindered by a lack of basic information on the number, identity, distribution and phylogenetic relationships of species. Available knowledge is restricted to studies on national and sub-national levels. The present study aims to resolve the diversity, biogeography and evolutionary relationships of the Far East Asian Unionidae in a globally comprehensive phylogenetic and systematic context. We reassessed the systematics of all Unionidae species in the region, including newly collected specimens from across Japan, South Korea, and Russia, based on molecular (including molecular species delineation and a COI + 28S phylogeny) and comparative morphological analyses. Biogeographical patterns were then assessed based on available species distribution data from the authors and previous reference works. We revealed that Unionidae species richness in Far East Asia is 30% higher than previously assumed, counting 43 species (41 native + 2 alien) within two Unionidae subfamilies, the Unioninae (32 + 1) and Gonideinae (9 + 1). Four of these species are new to science, i.e. Beringiana gosannensissp. nov., Beringiana fukuharaisp. nov., Buldowskia kamiyaisp. nov., and Koreosolenaia sitgyensisgen. & sp. nov. We also propose a replacement name for Nodularia sinulata, i.e. Nodularia breviconchanom. nov. and describe a new tribe (Middendorffinaiini tribe nov.) within the Unioninae subfamily. Biogeographical patterns indicate that this fauna is related to that from China south to Vietnam until the Mekong River basin. The Japanese islands of Honshu, Shikoku, Kyushu, Hokkaido, and the Korean Peninsula were identified as areas of particularly high conservation value, owing to high rates of endemism, diversity and habitat loss. The genetically unique species within the genera Amuranodonta, Obovalis, Koreosolenaiagen. nov., and Middendorffinaia are of high conservation concern.